Analisis Peranan Pelatihan Vokasi Oleh BPVP Banda Aceh Dalam Peningkatan Keterampilan Pengangguran Terdidik Lulusan Perguruan Tinggi Di Kota Banda Aceh - Situmeang, Marini Kristina; Azkia, Nora; Malih, Sa’I (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
Education, experience and skills are important indicators in fulfilling labor force participation. However, in reality, based on BPS data for 2021, the educated unemployment rate has increased from 6.69% in 2020 to 8.55% in 2021 of the total workforce with college graduates. The Job and Productivity Training Center (BPVP) as a formal educational institution has provided additional skills education for college graduates. This research was conducted using a qualitative research method with a descriptive approach with a field approach carried out by means of observation, interviews and documentation for three months and confirmed with a number of college graduate students, alumni, staff and facilitators. Field findings show a large influence in increasing the skills capacity of training participants. The Community Satisfaction Index (IKM) with services at the Banda Aceh Vocational and Productivity Training Center in Semester 1 of the 2023 Fiscal Year received an average score of 91. with the title of Very Good service unit performance.